Global analysis of typographical elements in logo design Home Marketing Centers (Malls) (Al-Academy, 2024)
The logos that are designed for specific purposes, such as the design logos of malls, bear typographical elements that represent pictorial symbols designed to express the distinctive feature of a product, company, service or entity in order to benefit in the process of distinguishing this mall from others and giving it an identity to describe the behavioral features of the nature of the mall and the level of services provided to the consumer.The problem of the current research was established in the mind of the researcher through his observation and observation of the logos designed for malls located in the city of Baghdad, as he deliberated in his mind to search for the components of these designs through a scientific analysis of the typographical elements included in those logos and to stand on the symbols of signs and their relationship to the content of the malls aimed at presenting services to the consumer, so the researcher put the following question:To what extent are the logos designed for the malls in Baghdad and the signs they bear consistent with typographical elements that give a suggestive indication of the place?The current research aims to reveal the typographical elements that form the signs in the formation shopping logos (malls(.Since the current research aims to (discover the typographical elements that form the signs in the formation shopping logos (the malls)), so the researcher adopts the descriptive analytical approach, as it is the most appropriate method to achieve the goal of the research.The research community consists of the slogans of the home shopping centers (the malls) scattered in the city of Baghdad, which were established after the year (2003) and numbered (22) home shopping centers, and the researcher obtained these slogans through the information network (Net), so he considered it a community for his research, A random sample was selected from the research community, which amounted to (2) samples from the research community.The most important results are: 1-The designer of the logo borrowed a symbol of civilization or heritage ... and others, as it represents strength, courage and dominance to give suggestive connotations of control and renewal, and it represents the goal of the shopping mall by bringing up everything new that meets the needs of the consumer.2- It appears that the logo designer was able to harmonize between the idea, the borrowed form and the writing to operate the typographical elements within the design space, as in the sample (1).